A PBT composite material and its preparation method and application

By adding specific components to the PBT composite material, the effect of reducing shrinkage defects and maintaining high toughness is achieved, and the problem of degradation of material toughness in the prior art is solved, and it is suitable for applications such as thick-walled parts.

CN117447818BActive Publication Date: 2025-03-28SHANGHAI KINGFA SCI & TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311573868.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-23
Publication Date
2025-03-28
Estimated Expiration
2043-11-23

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the toughness of the material while reducing the shrinkage defects of PBT materials, and the way of adjusting the crystallinity will affect the heat resistance of the material.

Method used

By adding components in a specific mass range to the PBT composite material, including PBT resin, reinforcement, expander, stabilizer and toughener, the components have excellent synergistic effects, achieving low specific gravity and no shrinkage of the product while maintaining high toughness.

Benefits of technology

It realizes the low specific gravity, no shrinkage and high toughness of PBT composite materials, and is suitable for thick-walled parts and other applications, and the preparation method is simple to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004566363800000071
    Figure BDA0004566363800000071
  • Figure BDA0004566363800000072
    Figure BDA0004566363800000072
  • Figure BDA0004566363800000081
    Figure BDA0004566363800000081
Patent Text Reader

Abstract

The invention discloses a PBT composite material and a preparation method and application thereof, belonging to the technical field of polymer materials; the PBT composite material provided by the invention comprises the following components by mass: 45-85 parts of PBT resin, 10-40 parts of reinforcing agent, 0.5-5 parts of swelling agent, 0.3-1.5 parts of stabilizer, and 1-8 parts of toughening agent; the intrinsic viscosity of the PBT resin is ≤1.12dl / g; the swelling agent is an organic matter with a boiling point between 210-310°C; the stabilizer is an epoxy resin or a polymeric carbodiimide. The PBT composite material provided by the invention has good toughness, low specific gravity and no shrinkage cavities. And the preparation method provided by the invention is simple to operate, which is conducive to practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a PBT composite material and a preparation method and application thereof. Background Art

[0002] In general, the shrinkage rate of crystalline materials is relatively large, and shrinkage defects are prone to occur in thick-walled parts or ribs. In the prior art solutions, there is a way to reduce shrinkage by adding fillers. For example, the prior art CN104387649A provides a special material for thick-walled PE pipe fittings with anti-shrinkage. The anti-shrinkage PE material is obtained by adding needle-shaped calcium carbonate whiskers, ethylene-propylene rubber, nano-calcium carbonate, etc. to achieve the anti-shrinkage effect of thick-walled parts; however, the introduction of fillers generally leads to a decrease in the shrinkage rate of the material, and the density is significantly increased, and the toughness of the material is also reduced. In addition, there is also a prior art that achieves the product without shrinkage by adjusting the degree of crystallinity. For example, the prior art CN115491031A provides a long carbon chain nylon molding compound, which reduces the crystallinity of the material by mixing resins with different fluidity and different crystallinity, thereby reducing shrinkage to improve the shrinkage problem; however, the method of adjusting the degree of crystallinity will lead to a decrease in shrinkage, and at the same time affect the heat resistance of the material.

[0003] PBT is a crystalline material with a large shrinkage rate. The shrinkage rate of conventional PBT resin exceeds 1.5%. When the thickness of the plastic part exceeds 6mm, there is a risk of shrinkage holes. PBT material has high strength, high density, and high rigidity, but its ability to resist deformation is weak, that is, its toughness is low. The existing technology for reducing shrinkage holes cannot simultaneously achieve the goal of reducing shrinkage holes while ensuring good toughness of the product. Therefore, it is very important to develop a PBT modified material that improves shrinkage defects and has excellent toughness. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a PBT composite material with low specific gravity, high toughness and no shrinkage cavities, and a preparation method and application thereof.

[0005] To achieve the above-mentioned purpose, in a first aspect of the present invention, the present invention provides a PBT composite material, which comprises the following components in parts by weight: 45-85 parts of PBT resin, 10-40 parts of reinforcing agent, 0.5-5 parts of expanding agent, 0.3-1.5 parts of stabilizer, and 1-8 parts of toughening agent; the intrinsic viscosity of the PBT resin is ≤1.12dl / g; the expanding agent is an organic matter with a boiling point between 210-310°C; and the stabilizer is an epoxy resin or a polymeric carbodiimide.

[0006] The PBT composite material provided by the present invention has excellent synergistic effects between the components by adding the above components in a specific mass range, and can achieve a low specific gravity of the product on the basis of adding less expansion agent and stabilizer, and the product has no shrinkage cavities. At the same time, due to the small amount of expansion agent and stabilizer added, it will not cause obvious damage to the toughness of the composite material. Specifically, when the characteristic viscosity of the PBT resin is ≤1.12dl / g, it can ensure that the matrix resin has the ability to open bubbles; the addition of the expansion agent is the root of the generation of micro-foaming, and the expansion agent with a boiling point between 210-310℃ is specifically selected. During the cooling process of the PBT composite material melt, the heat provided by the melt promotes the gasification of the expansion agent or the generation of inert gas, achieving a micro-foaming effect, and the foaming supplements the volume of the shrinkage of the melt, thereby avoiding the generation of shrinkage cavities, that is, micro-foaming and volume supplementation achieve the dual effects of low specific gravity and no shrinkage cavities. The molecular weight of PBT material will decrease after twin-screw shearing, resulting in a decrease in melt strength. The introduction of epoxy resin or polymeric carbodiimide as a stabilizer can increase the melt viscosity of the PBT composite material and improve the melt strength. At the same time, the two stabilizers can react with the end carboxyl groups of PBT to reduce the degradation of PBT polymer during extrusion modification and injection molding, and play an important role in the formation and stabilization of bubbles. That is, the addition of stabilizers can not only improve the melt strength, but also stabilize the micro-foaming produced by the expansion agent, so that the micro-foaming can achieve a dense and uniform effect, and the micro-bubbles can also terminate the silver streaks, thereby improving the cantilever beam notch impact strength of the product and achieving the purpose of improving toughness.

[0007] The specific viscosity of PBT resin is determined with reference to GB / T 14190-2017; specifically, the test is carried out using an Ubbelohde viscometer in a constant temperature water bath, the selected solvent is a mixed solvent of phenol and tetrachloroethane, the mass ratio of phenol:tetrachloroethane = 3:2, and the test temperature is 25°C.

[0008] The boiling point of the expansion agent is tested under standard atmospheric pressure. The principle of the method is that when the temperature of the liquid increases, its vapor pressure increases accordingly. When the vapor pressure of the liquid is equal to the atmospheric pressure, it begins to boil. The temperature at this time is the boiling point.

[0009] For example, in the PBT composite material, the proportion of the PBT resin can be any point value between 45 and 85 parts or a range of any two points, such as 45 parts, 48 ​​parts, 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, 82 parts, 85 parts, etc.; the proportion of the reinforcing agent can be any point value between 10 and 40 parts. The amount of the expander can be any point value between 0.5 and 5 parts or a range of any two points, for example, the amount of the expander can be 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 2, 2.2, etc. The number of stabilizers can be any point value between 0.3-1.5 parts or a range of any two points, for example, the number of stabilizers can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, etc.; the number of parts of the toughening agent can be any point value between 1-8 parts or a range of values ​​between any two points, for example, the number of parts of the toughening agent can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, etc.; due to space limitations, they are not listed here one by one, and the effects of the present invention can be achieved within the mass parts range of the components given in the present invention.

[0010] In the PBT composite material, the mass percentage of PBT resin is not less than 55%.

[0011] As a preferred embodiment of the PBT composite material of the present invention, the PBT composite material comprises the following components in parts by weight: 2-4 parts of an expander and 0.5-1 parts of a stabilizer.

[0012] The inventors have found that when the expansion agent is within an appropriate dosage range, a good balance can be achieved between the amount of foaming generated and the volume of the foaming; when the stabilizer is within an appropriate dosage range, it can stabilize the micro-foaming of the expansion agent while avoiding excessive stabilizer causing excessive melt viscosity and resulting in difficulty in foaming; further limiting the expansion agent and the stabilizer within the above-mentioned mass range can achieve a good synergistic effect of the stabilizer on the expansion agent, thereby achieving a more excellent comprehensive effect.

[0013] As a preferred embodiment of the PBT composite material of the present invention, the expansion agent is an organic substance with a boiling point between 241-305°C.

[0014] Exemplarily, the boiling point of the expansion agent may be any point value between 241-305°C or a range value between any two points, such as 241°C, 245°C, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, etc. Within the range of 241-305°C given in the present invention, a better comprehensive effect can be achieved.

[0015] As a preferred embodiment of the PBT composite material of the present invention, in the polymeric carbodiimide, the content of N=C=N functional groups is ≥15%.

[0016] The weight average molecular weight of the polymeric carbodiimide is 8000-30000.

[0017] Preferably, the content of N=C=N functional groups in the polymeric carbodiimide is 15-21%.

[0018] In carbodiimide, the content of N=C=N functional group is converted by the content of nitrogen. The nitrogen content is tested by nitrogen tester, instrument model: FlashSmart; instrument mode: N / protein Dumas nitrogen; furnace temperature: 950℃ (Oxidation) 840℃ (Reduction); carrier gas flow rate: 140ml / min; analysis time 450s. The weight average molecular weight is tested by GPC method according to GB / T 27843-2011, and the mobile phase is tetrahydrofuran.

[0019] As a preferred embodiment of the PBT composite material of the present invention, at least one of the following (a)-(d) is included:

[0020] (a) the intrinsic viscosity of the PBT resin is 0.7-1.05 dl / g;

[0021] (b) the swelling agent is at least one of dimethyl terephthalate, methyl paraben, ethyl paraben, methyl p-toluate, ethyl p-toluate, R-propylene carbonate, diphenyl carbonate, and dimethyl phthalate;

[0022] (c) the epoxy equivalent of the epoxy resin is 1700-3100 g / eg;

[0023] (d) The reinforcing agent is glass fiber.

[0024] The inventors have found that when the intrinsic viscosity of the PBT resin is further optimized to be 0.7-1.05dl / g, the composite material can have better melt strength, which is beneficial to the foaming of the PBT composite material and reduces the behavior of bubbles or bubbles. If there are too many bubbles or bubbles, the toughness of the composite material will decrease and the mechanical properties will also decrease.

[0025] Exemplarily, the intrinsic viscosity of the PBT resin may be any point value or a range value between any two points between 0.7 and 1.05 dl / g. For example, the intrinsic viscosity of the PBT resin may be 0.7 dl / g, 0.75 dl / g, 0.8 dl / g, 0.85 dl / g, 0.9 dl / g, 0.95 dl / g, 1.0 dl / g, 1.05 dl / g, etc. The effects of the present invention can be achieved within the range of 0.7 to 1.05 dl / g given in the present invention.

[0026] The inventors have found that when the expander is selected as the above components, the overall effect of the obtained product is better and more excellent.

[0027] The epoxy equivalent is tested with reference to GB / T 4612-2008 Determination of epoxy equivalent of plastic epoxy compounds.

[0028] Exemplarily, the epoxy equivalent of the epoxy resin can be any point value between 1700-3100 g / eg or a range value between any two points. For example, the epoxy equivalent of the epoxy resin can be 1700 g / eg, 1800 g / eg, 1900 g / eg, 2000 g / eg, 2100 g / eg, 2200 g / eg, 2300 g / eg, 2400 g / eg, 2500 g / eg, 2600 g / eg, 2700 g / eg, 2800 g / eg, 2900 g / eg, 3000 g / eg, 3100 g / eg, etc. The effect of the present invention can be achieved within the range of 1700-3100 g / eg given in the present invention.

[0029] The inventors have found that when the epoxy equivalent is further preferably within the above range, the obtained product has a lower density, better toughness and no shrinkage cavities.

[0030] The reinforcing agent described in the present invention is glass fiber; the present invention has no special restrictions on the initial length, fiber diameter, cross-sectional shape (round, flat, special-shaped), and fiber morphology (such as raw silk, coarse sand, and ground) of the glass fiber. It can be continuous glass fiber or chopped glass fiber. Alkali-free chopped glass fiber is preferred based on the effect of the mechanical properties obtained.

[0031] The addition of toughening agent in the present invention can improve the toughness of the product. When the addition amount is preferably 1-8 parts, the difficulty of foaming caused by excessive addition can be avoided on the basis of increasing toughness. The present invention has no particular limitation on the type of toughening agent. For example, the toughening agent can be at least one of ethylene-methyl acrylate-glycidyl methacrylate terpolymer, ethylene-butyl acrylate-glycidyl methacrylate terpolymer, glycidyl methacrylate grafted ethylene-butyl acrylate copolymer, glycidyl methacrylate grafted ethylene-methyl acrylate copolymer, ethylene-butyl acrylate, and ethylene-methyl acrylate.

[0032] As a preferred embodiment of the PBT composite material of the present invention, the PBT composite material further comprises 0-2 parts of a processing aid.

[0033] As a preferred embodiment of the PBT composite material of the present invention, the processing aid is at least one of an antioxidant, a lubricant, a nucleating agent, a laser aid, a weathering agent, and a hydrolysis resistance aid.

[0034] In a second aspect of the present invention, the present invention provides a method for preparing the PBT composite material, the method comprising the following steps: mixing the components uniformly and then melt-extruding to obtain the PBT composite material.

[0035] As a preferred embodiment of the preparation method of the present invention, the temperature of the melt extrusion is 200-240° C. For PBT composite materials, the general injection molding temperature is between 230-280° C.

[0036] In the third aspect of the present invention, the present invention provides the use of the PBT composite material in thick-walled parts in the fields of automobiles, water treatment, and electrical and electronic products.

[0037] For example, the application may be an application on a car door handle in the automotive field, a water pump component in the water treatment field, or a contactor connecting rod in the electrical and electronic field.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The PBT composite material provided by the present invention has excellent synergistic effects between the components by adding components in a specific mass range, and can achieve a low specific gravity of the product on the basis of ensuring the toughness of the prepared composite material, that is, it can achieve weight reduction of the product, which is conducive to the lightweight design of the product, and the product has no shrinkage holes. Specifically, the density of the obtained composite material is 1.37g / cm 3 Below, the Izod notch impact strength is 13.6 kJ / m 2 In the above, the number of shrinkage cavities is less than 1. In addition, the preparation method provided by the present invention is simple to operate and is conducive to practical application. DETAILED DESCRIPTION

[0040] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0041] Unless otherwise specified, the raw materials used in the present invention are conventional commercially available raw materials, and the raw materials used in the parallel embodiments or comparative examples of the present invention are consistent.

[0042] PBT-1: PBT GX121, intrinsic viscosity 1.00 dl / g, Sinopec Asset Management Co., Ltd. Yizheng Branch;

[0043] PBT-2: PBT KX9110, intrinsic viscosity 1.10 dl / g, Henan Kaixiang Tianyuan Chemical Co., Ltd.;

[0044] PBT-3: PBT GX111, intrinsic viscosity 0.73dl / g, Sinopec Asset Management Co., Ltd. Yizheng Branch;

[0045] PBT-4: PBT GX110, intrinsic viscosity 0.67dl / g, Sinopec Asset Management Co., Ltd. Yizheng Branch;

[0046] PBT-5: PBT GL236, intrinsic viscosity 1.28dl / g, Sinopec Asset Management Co., Ltd. Yizheng Branch;

[0047] Reinforcement: Glass fiber, alkali-free chopped glass fiber, ECS11-4.5-534A, Jushi Group Co., Ltd.;

[0048] Expanding agent 1: dimethyl terephthalate, CAS No. 120-61-6, boiling point 288°C, Anaiji Chemical Reagent;

[0049] Expanding agent 2: ethylparaben, CAS number 120-47-8, boiling point 297.5℃, Anaiji Chemical Reagent;

[0050] Expanding agent 3: R-propylene carbonate, CAS No. 16606-55-6, boiling point 241.7°C, Anaiji Chemical Reagent;

[0051] Expanding agent 3: R-propylene carbonate, CAS No. 16606-55-6, boiling point 241.72°C, Anaiji Chemical Reagent;

[0052] Expanding agent 4: di-o-cresyl carbonate, CAS number 617-09-4, boiling point 341°C, Anaiji Chemical Reagent;

[0053] Expanding agent 5: dibutyl carbonate, CAS No. 542-52-9, boiling point 207°C, Anaiji Chemical Reagent;

[0054] Stabilizer 1: epoxy resin, YD-019, epoxy equivalent weight 2500-3100 g / eq, Guodu Chemical (Kunshan) Co., Ltd.

[0055] Stabilizer 2: epoxy resin, YD-017, epoxy equivalent weight 1750-2100 g / eq, Guodu Chemical (Kunshan) Co., Ltd.

[0056] Stabilizer 3: polymeric carbodiimide, model number Stabilizer9000, weight average molecular weight of 25000-30000, N=C=N functional group content of 17-19%, Raschig GmbH;

[0057] Stabilizer 4: epoxy resin, KD-214M, epoxy equivalent weight 1150-1300 g / eq, Guodu Chemical (Kunshan) Co., Ltd.

[0058] Stabilizer 5: single molecule carbodiimide, model HyMax 1010, molecular weight 362, N=C=N functional group content 10-11%, Shanghai Langyi Functional Materials Co., Ltd.;

[0059] Toughening agent: ethylene-methyl acrylate-glycidyl methacrylate terpolymer, AX8900, Arkema China Investment Co., Ltd.;

[0060] Lubricant: oxidized polyethylene wax, commercially available;

[0061] Antioxidant: pentaerythritol tetrakis[β(3.5-di-tert-butyl-4-hydroxyphenyl)propionate, commercially available.

[0062] Examples 1-18 and Comparative Examples 1-9

[0063] Examples 1-18 of the present invention and comparative examples 1-9 provide a PBT composite material, the components (parts by mass) of the composite material are shown in Table 1-2;

[0064] Table 1

[0065]

[0066] Table 2

[0067]

[0068]

[0069] The preparation method of the PBT composite material provided in Examples 1-18 and Comparative Examples 1-9 is: after the components are uniformly mixed, melt-extruded at 230° C. to obtain the PBT composite material.

[0070] Effect example

[0071] This effect example verifies the performance of the PBT composite materials prepared in Examples 1-18 and Comparative Examples 1-9, specifically including the following aspects:

[0072] 1. Shrinkage cavity evaluation method: On a 90T Haitian injection molding machine, the size of the injection molding spline is 127*16*8mm, the injection temperature is 260℃, the injection pressure is 50%, the injection speed is 45%, there is no pressure holding, and the mold temperature is 20℃; the spline is cut horizontally 5mm away from the gate to observe whether there are shrinkage cavities visible to the naked eye; 10 splines are cut for each sample, and the number of splines with shrinkage cavities visible to the naked eye is recorded; shrinkage cavities refer to holes formed by cooling and shrinkage during the molding and curing process of the part, and the shrinkage cavities are usually irregular in shape and have rough hole walls;

[0073] 2. Izod notched impact strength: measured on a 90T Haitian injection molding machine with a molding strip size of 80*10*4mm, an injection temperature of 270°C, an injection pressure of 30%, an injection speed of 35%, and a holding pressure of 15% at room temperature according to ISO 180:2019;

[0074] The data obtained from the test are shown in Table 3;

[0075] Table 3

[0076]

[0077] It can be seen from Table 3 that when the technical solution provided by the present invention is adopted, the obtained PBT composite material has the characteristics of high toughness and few shrinkage holes. Among them, the Izod notched impact strength of the prepared PBT composite material is 13.6 kJ / m 2 Above, the number of shrinkage cavities is less than 1;

[0078] It can be seen from Example 1, Examples 4-9 and Comparative Examples 4-5 that the amount of expansion agent and stabilizer added will have a significant impact on the performance of the product; when the amount of expansion agent added in Comparative Example 4 is too much, the toughness of the obtained product decreases significantly, and the notched cantilever beam impact strength decreases by 47.3% compared with Example 1; when the amount of stabilizer added in Comparative Example 5 is too much, the performance of the obtained product decreases significantly, and the number of shrinkage cavities reaches 6; when the mass portion of the expansion agent is further preferably 2-4 parts and the mass portion of the stabilizer is 0.5-1 part, the comprehensive effect of the obtained product is better, and the notched cantilever beam impact strength of the prepared PBT composite material is 16.3 kJ / m 2As shown in the above, the shrinkage cavities are 0; it can be seen from Example 1 and Comparative Examples 1-3 that when neither the expander nor the stabilizer is added, or neither of them is added, the obtained products have obvious shrinkage cavities, and the number of shrinkage cavities is 5-10;

[0079] It can be seen from Example 1, Examples 11-13 and Comparative Example 6 that the intrinsic viscosity of the PBT resin will also affect the performance of the product; when the intrinsic viscosity of the PBT resin in Comparative Example 6 is not within the scope of the present invention, the obtained product has many shrinkage cavities, which are 6; when the intrinsic viscosity of the PBT resin is further preferably 0.7-1.05 dl / g, the obtained product has excellent comprehensive performance, and the Izod notched impact strength of the prepared PBT composite material is 15.9 kJ / m 2 Above, the number of shrinkage cavities is 0;

[0080] It can be seen from Example 1, Examples 14-15 and Comparative Examples 7-8 that the selection of the expansion agent will also affect the performance of the product; when the boiling point of the expansion agent selected in Comparative Examples 7-8 is not within the range of the present invention, the obtained product has many shrinkage pores;

[0081] It can be seen from Example 1, Examples 16-18 and Comparative Example 9 that the selection of the stabilizer will also affect the performance of the product; when the stabilizer selected in Comparative Example 9 is not the stabilizer of the present invention, the impact performance of the obtained product decreases and the shrinkage cavities increase; when the equivalent of the epoxy resin is further preferably within the range of the present invention, the comprehensive performance of the obtained product is excellent, and the Izod notched impact strength of the prepared PBT composite material is 16.3 kJ / m 2 Above, the number of shrinkage cavities is 0.

[0082] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A PBT composite material, characterized in that: The PBT composite material comprises the following components in parts by mass: PBT resin 45-85 parts, reinforcing agent 10-40 parts, expansion agent 0.5-5 parts, stabilizer 0.3-1.5 parts, toughening agent 1-8 parts; The intrinsic viscosity of the PBT resin is ≤1.12dl / g; the intrinsic viscosity of the PBT resin is measured with reference to GB / T14190-2017, and the test temperature is 25°C; The expansion agent is an organic substance with a boiling point between 210-310° C.; the expansion agent is at least one of dimethyl terephthalate, methyl paraben, ethyl paraben, methyl p-toluate, ethyl p-toluate, R-propylene carbonate, diphenyl carbonate, and dimethyl phthalate; The stabilizer is epoxy resin or polymeric carbodiimide.

2. The PBT composite material according to claim 1, characterized in that: The PBT composite material comprises the following components in parts by weight: 2-4 parts of an expander and 0.5-1 parts of a stabilizer.

3. The PBT composite material according to claim 1, characterized in that: The expansion agent is an organic substance with a boiling point between 241-305°C.

4. The PBT composite material according to claim 1, characterized in that: At least one of the following (a)-(c): (a) the intrinsic viscosity of the PBT resin is 0.7-1.05 dl / g; (b) the epoxy equivalent of the epoxy resin is 1700-3100 g / eg; (c) The reinforcing agent is glass fiber.

5. The PBT composite material according to claim 1, characterized in that: The PBT composite material also includes 0-2 parts of a processing aid.

6. The PBT composite material according to claim 5, characterized in that: The processing aid is at least one of an antioxidant, a lubricant, a nucleating agent, a laser aid, a weathering agent, and a hydrolysis resistance aid.

7. The method for preparing the PBT composite material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: mixing the components uniformly and then melt-extruding them to obtain a PBT composite material.

8. The preparation method according to claim 7, characterized in that: The temperature of the melt extrusion is 200-240°C.

9. Application of the PBT composite material according to any one of claims 1 to 6 in thick-walled parts in the fields of automobiles, water treatment, and electronics and electrical appliances.

Citation Information

Patent Citations

  • Special shrinkage-cavity prevention material for thick-wall PE (polyethylene) pipe and method for preparing same

    CN104387649A

  • Long-carbon-chain nylon molding compound for preparing shrinkage-cavity-free high-strength thick product

    CN115491031A

  • Intumescent high-glow-wire ignition temperature PBT (polybutylece terephthalate) composite material and preparation method thereof

    CN104327467A

  • PBT / PC alloy with stable mechanical properties, and preparation method therefor and article thereof

    WO2023279984A1